2004
DOI: 10.14214/sf.421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thawing duration and temperature on field performance of frozen-stored Norway spruce container seedlings

Abstract: Increasing use of frozen storage in nurseries at northern latitudes calls for thawing methods that are safe, economical and easy to apply on a large scale. The easiest and most economical method would be to thaw seedlings in the same boxes they were stored in. However, doing this safely requires more knowledge about how long and at what temperatures seedlings should or can be kept in the boxes without reducing field performance. In this study, 1-yr-old frozen-stored Norway spruce (Picea abies (L.) Karst.) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Overall, the safe storage periods for the non-dormant seedlings are shorter than those for freezer-stored seedlings, with the latter being storable for up to two weeks after the root plugs have thawed under cool conditions [10]. However, the storage period for non-dormant seedlings in closed boxes is about the same (about a week) as that for freezer-stored and properly thawed seedlings under warm conditions [10].…”
Section: Effects Of Storage Treatment On Field Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the safe storage periods for the non-dormant seedlings are shorter than those for freezer-stored seedlings, with the latter being storable for up to two weeks after the root plugs have thawed under cool conditions [10]. However, the storage period for non-dormant seedlings in closed boxes is about the same (about a week) as that for freezer-stored and properly thawed seedlings under warm conditions [10].…”
Section: Effects Of Storage Treatment On Field Performancementioning
confidence: 99%
“…The cardboard storage method was originally invented for dormant seedlings that can be stored in closed boxes in the freezer for several months without suffering a significant decrease in vigor [9]. Seedlings can be safely stored in closed boxes for up to two weeks after freezer storage in cool weather in spring, based on previous studies [10]. However, in practical forestry in Finland, freezer-stored seedlings are commonly kept in closed cardboard boxes for longer period than that [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thawing duration is thought to be one factor that could help avoid recrystallization and ensure the satisfactory recovery of vitrified material. Helenius et al (2004) reported that high thawing temperatures (>15 °C) would thaw frozen root plugs rapidly and could result in the depletion of carbohydrates. In our study, regrowth was obtained at 47% when the PLBs were thawed at 45 °C for 85 s after 4 weeks of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, during the summer months, the storage duration of seedlings in closed packaging cannot exceed 1-2 days (Luoranen et al 2019). This is the case even with freezer-stored seedlings if they are thawed, and air temperatures are high (Helenius et al 2004). Previously, Nilsson and Örlander (1995) and Luoranen et al (2005;2022a) also observed increased mortality in seedling material intended for spring plantings and planted late (July).…”
Section: Planting Periods and Growing Phase Of Seedlingsmentioning
confidence: 99%